2004
DOI: 10.1016/j.leukres.2003.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal p70S6K basal activity increases upon induction of differentiation of myelomonocytic leukemic cell lines HL60, AML14 and MPD

Abstract: The role of ribosomal p70S6K in the cell cycle has been studied extensively, and it is known that this enzyme is crucial for cell advancement through G(1). Conversely, the participation of p70S6K in cell differentiation is not well understood. We have studied the response of p70S6K to the cytokine granulocyte-macrophage colony stimulating factor (GM-CSF) in three differentiation-capable leukemic cell lines (MPD, AML-14 and HL-60) and in normal mature neutrophils. Immature leukemic cells starved for 16 h showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The data presented in Figure 8A show that MTLn3 ( 41 ) (rat breast cancer cells) demonstrate elevated cell invasion particularly with the overexpression of PLD2, Grb2 and WASP. Two other cancer cell lines, AML14-eosinophils (AML-14-Eo)( 45 ) and HL-60 neutrophilic (HL60-neut), both leukemic, also displayed similar patterns. Thus, the mechanistic findings could be extrapolated to other cell lines.…”
Section: Resultsmentioning
confidence: 81%
“…The data presented in Figure 8A show that MTLn3 ( 41 ) (rat breast cancer cells) demonstrate elevated cell invasion particularly with the overexpression of PLD2, Grb2 and WASP. Two other cancer cell lines, AML14-eosinophils (AML-14-Eo)( 45 ) and HL-60 neutrophilic (HL60-neut), both leukemic, also displayed similar patterns. Thus, the mechanistic findings could be extrapolated to other cell lines.…”
Section: Resultsmentioning
confidence: 81%
“…The promyelocytic HL60 cells were grown in RPMI-1640 (PAA) supplemented with L-glutamine (2 mM) and 10% fetal bovine serum (FBS) at 37°C with 5% CO 2 . Cell differentiation was triggered by addition of DMSO (1.75%) for 4 days (dHL60 cells) 40. To check the differentiation from undifferentiated (uHL60) to differentiated neutrophil-like (dHL60) cells: To check the differentiation from undifferentiated (uHL60) to differentiated neutrophil-like (dHL60) cells, CD11b surface expression was checked by flow cytometry with a CD11b-FITC antibody (1:30).…”
Section: Methodsmentioning
confidence: 99%
“…Ingenuity pathway analysis (IPA) demonstrated that canonical pathways involved in eukaryotic initiation factor 2 (EIF2) as well as in eEIF4 and p70S6K signaling were enriched in TANs from β-glucan-trained mice ( Figure 2 C). Whereas the p70S6K signaling pathway has been linked to granulocytic differentiation and neutrophil functions, such as chemotaxis ( Gomez-Cambronero et al., 2004 ; Gomez-Cambronero et al., 2003 ), the EIF2 signaling pathway has been associated with reactive oxygen species (ROS)-induced stress ( Liu et al., 2008 ; Zeeshan et al., 2016 ; Zhang and Kaufman, 2008 ). Given that neutrophil ROS are linked to the anti-tumor effects of neutrophils ( Granot et al., 2011 ; Yan et al., 2014 ), we focused next on the ROS pathway in TANs from β-glucan-trained mice compared with that in TANs from control-treated mice.…”
Section: Resultsmentioning
confidence: 99%